Probing relevant ingredients in mean-field approaches for the athermal rheology of yield stress materials. Issue 38 (21st August 2015) - Puosi, Francesco; Olivier, Julien; Martens, Kirsten
Abstract : Coarse-graining flow dynamics of amorphous systems: mesoscopic scale stress fluctuations are created by the elastic response to surrounding yielding events. Abstract : Although the notion of mechanical noise is expected to play a key role in the non-linear rheology of athermally sheared amorphous systems, its characterization has so far remained elusive. Here, we show using molecular dynamic simulations that in spite of the presence of strong spatio-temporal correlations in the system, the local stress exhibits normal diffusion under the effect of the mechanical noise in the finite driving regime. The diffusion constant appears to be proportional to the mean plastic activity. Our data suggests that the corresponding proportionality constant is density independent, and can be directly related to the specific form of the rheological flow curve, pointing the way to a generic way of modeling mechanical noise in mean-field equations.